2004
DOI: 10.1111/j.1048-891x.2004.14408.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential in vitro effects of chemotherapeutic agents on primary cultures of human ovarian carcinoma

Abstract: The treatment of ovarian cancer principally relies on the use of platinum and taxane chemotherapeutic agents. Short-term clinical results have been encouraging, but long-term responses remain limited. In this report, an in vitro assay system that utilizes cells grown from human tumor explants has been used to quantitatively evaluate responses to relevant concentrations of alternative chemotherapeutic agents. The results suggest that there are significant differences in the responses of explant-derived cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The current study was designed to evaluate the effectiveness of the ChemoFx Ò assay in predicting outcome following chemotherapy in women with ovarian cancer. This assay is designed to select the relevant epithelial ovarian carcinoma cells for testing, to determine the relative cell survival at a range of doses from below to above peak plasma level, to test combinations of drugs, and to determine the degree of response, that is, sensitivity as well as resistance (14)(15)(16)(17)(18) . As such, this assay is designed to identify chemotherapeutic agents to which the patient is likely to be resistant and to identify agents to which the patient's tumor is most likely to be sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study was designed to evaluate the effectiveness of the ChemoFx Ò assay in predicting outcome following chemotherapy in women with ovarian cancer. This assay is designed to select the relevant epithelial ovarian carcinoma cells for testing, to determine the relative cell survival at a range of doses from below to above peak plasma level, to test combinations of drugs, and to determine the degree of response, that is, sensitivity as well as resistance (14)(15)(16)(17)(18) . As such, this assay is designed to identify chemotherapeutic agents to which the patient is likely to be resistant and to identify agents to which the patient's tumor is most likely to be sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…A possible critique of ex vivo assay-assisted therapy is that it might simply define those tumors that are inherently more likely to be sensitive or resistant to chemotherapy in general, implying that assay-assisted chemotherapy would have no impact on patient outcome. Certainly, previous reports have shown that patients display different degrees of response ex vivo to various chemotherapy agent(s), with a subset being predominantly sensitive or resistant to most agents (9,10,(12)(13)(14)(15)(16)(17)(18) . In the current series, 20% of cases could be considered generally sensitive to chemotherapy and 13% generally resistant while the remaining two thirds of tumor specimens demonstrated considerable heterogeneity of response to the different drug(s) tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The assay results obtained and reported by Precision Therapeutics are grouped into three categories:…”
Section: Assaymentioning
confidence: 99%